Understanding the recruitment and selection processes of management accountants: An explorative study - Lauri Lepistö; Eeva-Mari Ihantola (Emerald Group Publishing Ltd, 2022)
Purpose – This paper aims to focus on the recruitment and selection processes of management accountants
to enhance the understanding of how employers form perceptions of a suitable management accountant.
Design/methodology/approach – The analysis is based on 17 interviews with individuals involved in
the recruitment of management accountants. Empirical data were collected during the recruitment process at
eight organisations.
Findings – The findings suggest that in the social context of recruitment, technical skills and abilities
related to management accounting are increasingly perceived as “taken for granted”, and employers instead focus on evaluating candidates’ appearance and overall credibility. In particular, employers look for
individuals who appear to be sociable, dynamic and appealing. Thus, a candidate’s overall appearance and
personality are central to the recruitment process, both of which are assessed through characteristics and
traits associated with personal charisma.
Practical implications – The findings have practical implications for both job seekers and recruiters of management accountants.
Originality/value – This study complements past studies on the role and image of management accountants by elucidating the social nature of their recruitment and selection. Keywords Management accounting, Selection, Recruitment, Management accountants
Paper type Research paper